Properties of Mucoid Serotype 3 Streptococcus pneumoniae From Children in China - Yang, Ying; Hua, Chun-Zhen; Fang, Chao; Xie, Yong-Ping; Li, Wei; Fu, Yong; Gao, Feng; Yao, Kai-Hu (Frontiers in Cellular and Infection Microbiology, 2021)
Objective: To investigate the characteristics of hosts, antimicrobial susceptibility, and molecular epidemiology of mucoid serotype 3 Streptococcus pneumoniae (S. pneumoniae) isolated from children in China. Method: S. pneumoniae isolates collected between January 2016 and December 2019 were analyzed. S. pneumoniae isolates with mucoid phenotype were selected visually, and serotype 3 isolates were confirmed by Quellung reaction. The antimicrobial susceptibility was measured by E-test. Multilocus sequence typing was used for clonal analysis. Results: Twenty (3.04%) isolates of mucoid serotype 3 S. pneumoniae were identified from 657 clinical isolates, and all of them were noninvasive strains. The average age of the hosts was 5.69±3.28 years. The isolates included: 50.0% from the dissected tonsil or adenoid tissue in children with obstructive sleep apnea-hypopnea syndrome, 45.0% from sputum or bronchial lavages in children with pneumonia, and 5.0% from vaginal secretions of one patient with vulvovaginitis. All isolates were sensitive to penicillin, cefuroxime, ceftriaxone, meropenem, vancomycin, levofloxacin, trimethoprim/sulfamethoxazole, and rifampin but resistant to erythromycin. Sequence type (ST)505 and its clonal complex (CC) were the main genotypes (95%). Antimicrobial susceptibility of ST180 and ST505 were compared, and the minimum inhibitory concentration (MIC) of ST505 isolates was significantly higher than that of ST180 for tetracycline, trimethoprim/sulfamethoxazole, and meropenem. Conclusions: Mucoid serotype 3 Streptococcus pneumoniae can be isolated from various body parts, among which the respiratory system is the most common. It can cause noninvasive infection in children, and it has high susceptibility to a variety of antibiotics, especially β-lactams, but is resistant to macrolides. CC505 is the novel clonal complex found in China, which may be related to the worldwide mainstream clonal complex (CC180) but has its own biological characteristics.